Blackfish Optimization Algorithm for Solving Reactive Power Problem - K. Lenin; B. Ravindhranath Reddy; M. Surya Kalavathi (IAES Indonesian Section, 2016)
In this paper Blackfish Algorithm (BA) has been utilized to solve the optimal reactive power problem. BA is inspired from bubble net hunting strategy of the black fish. In this algorithm roulette wheel selection method has been used to improve the convergence rate. The proposed BA has been tested in standard IEEE 30 bus test system and simulation results show clearly about the better performance of the proposed algorithm in reducing the real power loss with control variables within the limits.